An examination of works for band: Fortress variants by Elliot Del Borgo, Reflections by James Swearingen, Equinox by Ed Huckeby, and Procession of the nobles (Rimsky-Korsakov) arranged by Andrew Balent - Saarinen, Margaret (Kansas State University, 2008)
This document contains historical, theoretical and lesson plans of the selected literature for the Graduate Conducting Recital of Margaret Saarinen. The conducting recital was held in the Performing Arts Center, Victor Valley College, in Victorville, California, Thursday, May 15, 2008 at 7:30 P.M. with performers from the College Band of Victor Valley College. Selections included Fortress Variants, by Elliot Del Borgo; Reflections, by James Swearingen; Equinox, by Ed Huckeby; and Procession of the Nobles (Rimsky-Korsakov) arranged by Andrew Balent.
Keywords: Del Borgo; Swearingen; Huckeby; Balent; Music (0413)